Experimental determination of droplet collision rates in turbulence - R Bordás; Ch Roloff; D Thévenin; R A Shaw (New Journal of Physics, 2013)
Inter-particle collisions in turbulent flows are of central importance for many engineering applications and environmental processes. For instance, collision and coalescence is the mechanism for warm rain initiation in cumulus clouds, a still poorly understood issue. This work presents measurements of droplet–droplet interactions in a laboratory turbulent flow, allowing reproducibility and control over initial and boundary conditions. The measured two-phase flow reproduces conditions relevant to cumulus clouds. The turbulent flow and the droplet size distribution are well characterized, and independently the collision rate is measured. Two independent experimental approaches for determining the collision rate are compared with each other: (i) a high-magnification shadowgraphy setup is employed, applying a deformation threshold as collision indicator. This technique has been specifically adapted to measure droplet collision probability in dispersed two-phase flows. (ii) Corresponding results are compared for the first time with a particle tracking approach, post-processing high-speed shadowgraphy image sequences. Using the measured turbulence and droplet properties, the turbulent collision kernel can be calculated for comparison. The two independent measurements deliver comparable orders of magnitude for the collision probability, highlighting the quality of the measurement process, even if the comparison between both measurement techniques is still associated with a large uncertainty. Comparisons with recently published theoretical predictions show reasonable agreement. The theoretical collision rates accounting for collision efficiency are noticeably closer to the measured values than those accounting only for transport.